MAXIMIZING THE ROBUST STABILITY DEGREE OF SYSTEM WITH INTERVAL CHARACTERISTIC POLYNOMIAL - Alexander V. Sobol; Sergey A. Gayvoronskiy (Известия Томского политехнического университета: Промышленная кибернетика)
The article considers the use of critical root diagrams for the synthesis of a one-parameter robust controller that provides the maximum stability degree in a third-order system with interval parameters. For the synthesis of the controller, the characteristic polynomial of the system is used, the coefficients of which are given by their own intervals. On critical root diagrams, the dominant roots of the characteristic polynomial are located on one vertical straight line, which determines the maximum degree of stability. The authors have developed the algorithm for synthesizing a controller at the vertices of a polyhedron of polynomial coefficients, which are possible prototypes of the dominant poles of critical diagrams. A numerical example is given.